DETECTION TOOL FOR BORAX PRESERVATIVE IN FOOD - Fatiatun, Fatiatun; Rahayu, Gusrina; Khumaeroh, Nadia; Wibowo, Kusnanto Mukti (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2024)
Currently, the use of prohibited food additives is still often found, and is even increasing, especially among food entrepreneurs, which are generally produced by small industries or households. One type of food preservation that is currently widely used is borax and formalin. The aim to be achieved in this research is to determine the characteristics of the tool for detecting preservatives (borax) in food and to determine the presence/absence of preservatives (borax) in meatball food. The method used in this research is experiment. The results obtained in this research can conclude that there is still use of borax in meatball type food although it is not yet known whether the seller actually uses borax on purpose or the flour used contains borax without the seller knowing it and the borax content itself greatly influences the results of the Frequency value.